Multiple ovulation was positively associated with milk yield independently of circulating progesterone concentrations in multiparous high-producing Holstein cows submitted to Double-Ovsynch - T.J. Valdés-Arciniega; E. Anta-Galván; I.M.R. Leão; T.O. Cunha; M.S. El Azzi; N.B. Cook; J.P.N. Martins (Journal of Dairy Science)
ABSTRACT: The present study aimed to determine the relationship between circulating progesterone (P4) concentrations and milk yield during the ovulatory follicular wave on the proportion of multiple ovulation (MOV) in multiparous high-producing Holstein cows (n = 1,345). The study used first-service multiparous cows submitted to a Double-Ovsynch program (GnRH; 7 d later, PGF2α; 3 d later, GnRH; 7 d later, GnRH [G1]; 7 d later, PGF2α [PG1]; 1 d later, PGF2α; ∼32 h later, GnRH [G2]; ∼16 h later, timed AI [TAI]). To assess ovulatory response and proportion of MOV, ovarian ultrasonography examinations were performed at G1 (n = 1,215) and G2 (n = 1,345) and from 40 to 48 h after each GnRH. Average milk yield (kg/d) for the weeks before G1 and PG1 were recorded. Blood samples were collected at G1 (n = 1,242) and PG1 (n = 1,333) to measure serum P4 concentrations. Milk yield for the 2 weeks before PG1 was 56.0 ± 0.2 kg/d. Overall, ovulation to G1 was 71.5%, and MOV to G1 was 16.6%. Circulating P4 concentration at G1 was higher in cows with single ovulation (SOV) at G1 than in cows with MOV (4.31 ± 0.08 vs. 3.70 ± 0.20 ng/mL, respectively). Overall, ovulation to G2 was 90.2%, and MOV to G2 was 13.7%. Cows with MOV to G2 also had lower P4 concentration at PG1 than cows with SOV (7.24 ± 0.28 vs. 8.91 ± 0.11 ng/mL, respectively). The interaction of serum P4 tertiles at PG1 × milk yield tertiles was not significant for MOV to G2. Nevertheless, independent of each other, MOV to G2 was positively associated with milk yield and negatively associated with serum P4 at PG1. The proportion of cows with MOV to G2 was greater for cows with previous MOV to G1 (32.9%) than for cows with SOV to G1 (9.8%). In summary, MOV in multiparous high-producing Holstein cows was highly associated with serum P4 concentrations, milk yield, and previous MOV. In addition, an increased proportion of MOV was associated with high milk yield tertile (≥58.5 kg/d) regardless of the serum P4 concentrations during the growth of the ovulatory follicle.